Amnestus raunoi J. A. Lis, the only representative of the Amnestinae in the Old World: a synonym of Amnestus pusillus Uhler (Hemiptera: Heteroptera: Cydnidae) - Martinez, Cristina Mayorga; Peredo, Luis Cervantes; Lis, Jerzy A. (Zootaxa, 2012)
The genus Amnestus was described by Dallas in 1851, as a New World genus, and it was ratified by Froeschner (1960) in his revision for the Western Hemisphere Cydnidae.